The Effectiveness of M.D-Risti Application as an Alternative for Independent Early Detection of Risk of Pregnancy during the Pandemic COVID-19 in Palu City, Central Sulawesi, Indonesia - Suarayasa, Ketut; Bangkele , Elli Yane; Sumarni, Sumarni; Harun, Haerani; Bohari, Bohari (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Early detection of risk factors for pregnancy is carried out through regular prenatal examinations from an early age to detect abnormalities/disorders/illnesses suffered by pregnant women early. Mobile applications are very helpful in the process of early detection and recording of health workers’ reports, especially during a pandemic. AIM: This study aims to assess the knowledge, attitudes, actions, and skills of pregnant women in the early detection of high-risk pregnancy before and after the intervention and the effectiveness of M.D-Risti modules and applications. METHODS: This study used a quasi-experiment design research design with a pre-post only group design consisting of an intervention group and a control group at 4 health centers in Palu City with a purposive sampling technique of 43 respondents per group with univariate and bivariate analysis. RESULTS: The results showed that there was a significant difference in the level of knowledge (p = 0.00), attitude (p = 0.00), action (p = 0.00), and the skills of pregnant women in early detection of pregnancy (p = 0.00) before and after treatment in the intervention group. There was a significant difference between the two groups with a significant value on knowledge (p = 0.00), attitude (p = 0.00), action (p = 0.00), and skills of pregnant women in doing early detection of pregnancy risk independently (p = 0.00). CONCLUSION: The intervention of M.D-Risti modules and applications had a significant effect on changes in knowledge, attitudes, actions, and skills of pregnant women in early detection of pregnancy risk compared to pregnant women who were not given intervention at all. The M.D-Risti application is one of the solutions during the COVID-19 pandemic and in the long term, all health centers in Palu city can use it to help monitor the risk of pregnancy more quickly